TDP-43 as a potential retinal biomarker for neurodegenerative diseases - Glashutter, Margit; Wijesinghe, Printha; Matsubara, Joanne A. (Frontiers in Neuroscience, 2025)
TDP-43 proteinopathies are a spectrum of neurodegenerative diseases (NDDs) characterized by the pathological cytoplasmic aggregation of the TDP-43 protein. These include amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), Alzheimer’s disease (AD), chronic traumatic encephalopathy (CTE), and others. TDP-43 in the eye shows promise as a biomarker for these NDDs. Several studies have identified cytoplasmic TDP-43 inclusions in retinal layers of donors with ALS, FTLD, AD, CTE, and other conditions using immunohistochemistry. Our findings suggest that pathological aggregates of TDP-43 in the human retina are most prevalent in FTLD-TDP, ALS, and CTE, suggesting these diseases may provide the most reliable context for studying the potential of TDP-43 as a retinal biomarker. Animal model studies have been pivotal in exploring TDP-43’s roles in the retina, including its nuclear and cytoplasmic localization, RNA binding properties, and interactions with other proteins. Despite these advances, more research is needed to develop therapeutic strategies. A major limitation of human autopsy studies is the lack of corresponding brain pathology assessments to confirm TDP-43 proteinopathy diagnosis and staging. Other limitations include small sample sizes, lack of antemortem eye pathology and clinical histories, and limited comparisons across multiple NDDs. Future directions for the TDP-43 as a retinal biomarker for NDDs include retinal tracers, hyperspectral imaging, oculomics, and machine learning development.